The inner nuclear membrane protein Lem2 coordinates RNA degradation at the nuclear periphery - Martín Caballero, Lucía; Capella, Matías; Barrales, Ramón Ramos; Dobrev, Nikolay; van Emden, Thomas; Hirano, Yasuhiro; Suma Sreechakram, Vishnu N.; Fischer-Burkart, Sabine; Kinugasa, Yasuha; Nevers, Alicia; Rougemaille, Mathieu; Sinning, Irmgard; et al. (Nature structural & molecular biology, 2022)
Transcriptionally silent chromatin often localizes to the nuclear periphery. However, whether the nuclear envelope (NE) is a site for post-transcriptional gene repression is not well understood. Here we demonstrate that Schizosaccharomyces pombe Lem2, an NE protein, regulates nuclear-exosome-mediated RNA degradation. Lem2 deletion causes accumulation of RNA precursors and meiotic transcripts and de-localization of an engineered exosome substrate from the nuclear periphery. Lem2 does not directly bind RNA but instead interacts with the exosome-targeting MTREC complex and its human homolog PAXT to promote RNA recruitment. This pathway acts largely independently of nuclear bodies where exosome factors assemble. Nutrient availability modulates Lem2 regulation of meiotic transcripts, implying that this pathway is environmentally responsive. Our work reveals that multiple spatially distinct degradation pathways exist. Among these, Lem2 coordinates RNA surveillance of meiotic transcripts and non-coding RNAs by recruiting exosome co-factors to the nuclear periphery.
Gesehen am 25.01.2023